Adhesive loose packings of small dry particles1. Issue 32 (28th August 2015) - Liu, Wenwei; Li, Shuiqing; Baule, Adrian; Makse, Hernán A.
<x xml:space="preserve">Abstract</x> We explore adhesive loose packings of small dry spherical particles of micrometer size using 3D discrete-element simulations with adhesive contact mechanics and statistical ensemble theory. A dimensionless adhesion parameter Ad successfully combines the effects of particle velocities, sizes and the work of adhesion, identifying a universal regime of adhesive packings for Ad > 1.